Attitudes of academic elites towards national identityA survey study of a purposive sample of university professors - Ahmed Sahi Hammadi Al-Saedi, Lect. Dr.; Mohammed Sabah , Lect. Dr. (lark, 2025)
This study explores the attitudes of academic elites who follow government websites and various digital social media platforms between July 1, 2024, and November 30, 2024. The aim is to identify the main trends adopted by university professors to understand the views and attitudes of this important elite group regarding the actions of the Iraqi government as presented through search engines and related social media platforms. The study was conducted using a purposive sample of 200 participants from the academic elites of Iraqi universities (Baghdad,, Al-Imam Al-Kadhim College, Al-Iraqiya, and Urok), all of whom follow these digital accounts. The goal is to obtain accurate scientific results that contribute to understanding Iraq's national identity through these digital windows, which are utilized in a scientific, methodological, and objective manner, relying on modern media technologies.
Keywords: National identity, digital national identity, academic elites